(untitled) (Homoeopathy for All, 2025)
Background: Primary infertility is the inability of a couple to conceive after at least one year of regular, unprotected intercourse, with no prior pregnancies. Endometriosis is a leading cause of infertility. Endometriosis is the occurrence of ectopic benign endometrial tissue outside the cavity of the uterus. Several theories have been propounded to explain endometriosis; with retrograde menstruation is the most suitable explanation for the development of this disease. Mainly presented with dysmenorrhea, dyspareunia and infertility due to adhesions (blocking the fallopian tubes), hormonal distrubances. While conventional management often involves surgical interventions to remove adhesions. Recurrence is not uncommon. Objectives: The objective of this case report is to document the clinical outcome of individualised homoeopathic management in a patient with primary infertility due to endometriosis and to evaluate its therapeutic potential as an alternative in gynaecological disorders. Method: a 31-year-old female presented with primary infertility for 5 years. Diagnosed clinically as primary infertility and endometriosis. The case was analysed in detail, and individualised homoeopathic treatment was prescribed based on the totality of symptoms. Lycopodium clavatum in fifty-millesimal (LM) scale was administered, starting from 0/1 to 0/6 over a period of three months. Clinical progress was monitored regularly, and treatment outcomes were assessed through symptom resolution and ultrasound sonography (USG). Result: The patient showed significant improvement and she conceived after three months of treatment. Photographic evidence of USG documented the clinical progress. The high total score (+8) on the MONARCH scale established a possible causal relationship between the homoeopathic intervention and the patient’s clinical improvement. Conclusion: In this case, individualised homoeopathic treatment with Lycopodium clavatum was effective in managing endometriosis related infertility within a plausible time frame. Further documentation and studies are warranted to substantiate these findings in the future.